Marketing Communication Strategy for the Digital Instagram Account of the Sumatera Baru Jewelry Store in Increasing Customer Trust in the Digital Age - Najwa Puteri Madani; Azwar Azwar (Green Publisher Indonesia, 2025)
The development of digitalization is changing consumption patterns and consumer behavior, as well as highlighting the inequality of MSMEs' adaptation to digital technology in Indonesia. In the context of the jewelry industry, which has high value and requires strong trust, Toko Mas Sumatra Baru is undergoing digital transformation through Instagram to build customer trust. This study aims to analyze the digital marketing communication strategy of Toko Mas Sumatra Baru in increasing customer trust. The method used was qualitative descriptive, with data collection through observation of the store's Instagram activities and semi-structured interviews with store owners, cross-generational customers, and digital marketing practitioners. Data analysis was based on the AISAS model and the 7P marketing mix. The results of the study show that Instagram is used primarily as a digital catalog and an educational medium that strengthens the store’s transparency and credibility. Collaboration with state-owned enterprises engaged in mortgage-based financing and microfinance services enhances transaction integrity and security, while educational content and customer testimonials help build benevolence-based trust. However, inconsistent upload frequency and limited digital interaction remain challenges. In conclusion, the combination of offline reputation and digital visual evidence through a systematic communication strategy on Instagram plays an important role in building customer trust. The research recommends improving content consistency, optimizing digital features, enhancing HR training, and applying data-driven digital marketing strategies to increase customer trust and store competitiveness in the digital age.